ANALYSIS OF THE EFFECTIVENESS OF LOCAL ORIGINAL INCOME SOURCES IN CENTRAL LOMBOK DISTRICT BEFORE AND AFTER THE MANDALIKA SPECIAL EKONOMMIC ZONE (SEZ) WAS BUILT - Alwi, Muhammad (Jurnal Aplikasi Perpajakan, 2025)
The aims of this research is to analize the effectiveness of sources Local Original Income before and after the construction of Mandalika SEZ ( = KEK). The analytical tool used in this research is Ratio of revenue Realisation to Target. The effectiveness of local taxes was quite higer before The Mandalika KEK was built compare to after Mandalika KEK was built. The effectiveness of Retribution regional levies was less effective both before and after the construction of the Mandalika KEK. The effectiveness of levies from Regiuonal Wealth Management yield before the mandalika KEK wqs built was very effective compare to after to The Mandalika KEK was built. The effectiveness of levies of other legitimate local original income before and after the construction of The Mandalika KEK is very effective. The effectiveness of levies on sources of Local Original Income is very dependent on the accuracy of determining targets and Taxpayer Complience in paying regional Taxes. Even though the level of effectiveness is’t fixed, sometimes very effective and sometimes not effective, The Local Original Income after the construction The Mandalika KEK from 2018 to 2023 is quite higer namely on average of IDR 212.372.o74 much greater then before the The Mandalika KEK wass built. The average of Local original income after The Mandalika KEK was built was IDR 200.025.312,2 and the average The Local Original Incoime before the Mandalika KEK wqs only IDR 174.717.156 or increase of 14.48 %. Key ward: Effectiveness of levies on sources of original regional income